Chemical Composition and Bioactivities of Essential Oil from Leaves of Syzygium cumini (L.) Skeels Native to Punjab, Pakistan. Issue 8 (10th July 2020) - Hanif, Muhammad Usman; Hussain, Abdullah Ijaz; Aslam, Nosheen; Kamal, Ghulam Mustafa; Chatha, Shahzad Ali Shahid; Shahida, Shabnam; Khalid, Muhammad; Hussain, Riaz
Abstract: Herbal medicines are widely used for the treatment of different types of diseases like skin and throat infections and other diseases in developing countries. Syzygium cumini (L.) Skeels fruit, leaves and bark were used for the remedies of different diseases anciently. The aim of the present study was to evaluate the chemical profile of Syzygium cumini leaves essential oil (EO) from Punjab, Pakistan. The essential oil was isolated using hydrodistillation technique and analyzed by gas chromatography (GC) and gas chromatography‐mass spectrometry (GC/MS). Free radical scavenging capacity and antioxidant activity were assessed by using DPPH radical scavenging ability, inhibition of linoleic acid peroxidation, bleaching of β ‐carotene in linoleic acid system and reducing power assays. Antimicrobial potential was assessed by disc diffusion assay and measurement of minimum inhibitory concentration (MIC) using resazurin microtiter‐plate assay. The anti‐heme biocrystallization activity of EO was also assessed. The major components (>3%) found in Syzygium cumini leaves EO were β ‐farnesene (3.42 %), caryophyllenol (3.46 %), terpinen‐4‐ol (3.61 %), β ‐myrcene (3.90 %), γ ‐cadinene (4.09 %), fenchol (4.22 %), cis‐β ‐ocimene (4.40 %) and 5‐methyl‐1, 3, 6‐heptatriene (4.90 %). Excellent antioxidant, antimicrobial and weak antimalarial potential was observed. It can be concluded that Syzygium cumini leaves EO has potential application for food and pharmaceutical industries. Abstract :